U.S. politics and the American macroeconomy - Fox, Gerald T. (Economics collection., 2015)
This book considers the interrelation among macroeconomic politics, macroeconomic policymakers, macroeconomic policies, and macroeconomic performance. This interaction is examined using the expectational Phillips curve model, which measures macroeconomic outcomes in terms of inflation and unemployment. In this book, the subject of macroeconomic politics mainly focuses on voter behavior, presidential re-election ambition, and political party priorities. These factors influence the macroeconomic policy actions of the president, Congress, and the central bank. This analysis takes into account both fiscal and monetary policies. Our examination of citizen sentiment is based on rational voter theory and the median voter model. We compare the effects of macroeconomic farsightedness versus shortsightedness among voters. We also contrast the conservative versus liberal perspectives on macroeconomic policy and performance. The empirical component of our analysis examines the electoral and partisan political business cycle effects upon the U.S. economy, and we find evidence of idiosyncratic effects during the time frame of 1961 through 2014. Finally, we discuss macroeconomic influence on various measures of voter sentiment, such as presidential job approval as well as presidential and congressional election outcomes.